2015
DOI: 10.3390/catal5042134
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Yolk/Core-Shell Structured TS-1@Mesosilica Composites for Enhanced Hydroxylation of Phenol

Abstract: In the current work, we developed a facile synthesis of yolk/core-shell structured TS-1@mesosilica composites and studied their catalytic performances in the hydroxylation of phenol with H2O2 as the oxidant. The core-shell TS-1@mesosilica composites were prepared via a uniform coating process, while the yolk-shell TS-1@mesosilica composite was prepared using a resorcinol-formaldehyde resin (RF) middle-layer as the sacrificial template. The obtained materials were characterized by X-ray diffraction (XRD), N2 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…New types of catalysts for efficient oxidation of carbon-hydrogen compounds have been reported in recent years: heteropolycompounds [107][108][109][110], supported complex catalysts [111,112], and porous materials [113][114][115][116][117][118][119][120][121][122].…”
Section: New Catalysts and Ligandsmentioning
confidence: 99%
“…New types of catalysts for efficient oxidation of carbon-hydrogen compounds have been reported in recent years: heteropolycompounds [107][108][109][110], supported complex catalysts [111,112], and porous materials [113][114][115][116][117][118][119][120][121][122].…”
Section: New Catalysts and Ligandsmentioning
confidence: 99%
“…S1a-d, ESI †), which was similar to the phenomenon in most core-shell molecular sieves. 30,31 The N 2 adsorption-desorption isotherms were shown in Fig. S2, ESI † and the corresponding physicochemical properties were summarized in Table S1, ESI.…”
Section: Resultsmentioning
confidence: 99%
“…TS-1, a Ti-containing MFI (Mordenite Framework Inverted) structure zeolite, first synthesized in 1983 by Taramasso et al [14], has been found to display excellent catalytic activity in the oxidation of the aromatic ring, such as aromatic hydroxylation and cyclohexanone ammoximation [15][16][17][18]. A TS-1-catalyzed reaction can proceed under mild conditions with aqueous H 2 O 2 as the oxidant so as to satisfy the demand of environmental protection.…”
Section: Introductionmentioning
confidence: 99%